Literatur Reviu Keterampilan Proses Sains sebagai Dasar Pengembangan Keterampilan Berpikir Tingkat Tinggi - Asy'ari, Muhammad; Fitriani, Herdiyana (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2017)
This article aims to describe empirically and theoretically the role of science process skills as a basis for learning high-level thinking skills. Science process skills are skills that are able to answer the demands of learning in accordance with the principles of constructivism related to the nature of science learning which is divided into three categories, namely (1) basic science process skills, (2) intermediate science process skills, and (3) science process skills high. Science process skills are claimed by many experts as the basis for developing high-level thinking skills. Activities such as (1) observation allow a person to be open to inquiry and be sensitive and willing to observe, (2) comparison, (3) classification, (4) measure, (5) communication, (6) inference, (7) prediction , (8) hypotheses, and (9) define and control variables, are activities in science process skills that are indispensable as basic skills to be able to think higher through integration in the learning process. High-level thinking skills such as critical thinking, creative thinking, and problem solving can be built through science learning that emphasizes the process. Critical thinking skills which are reflective processes in analyzing and evaluating information to determine one's beliefs and behavior can be built through creative processes that are lues, flexible, original, and precise in the stages of problem solving identification, planning, implementation and reflection.